1991
DOI: 10.1002/ar.1092310212
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycoconjugate expression during early chick embryo development: A lectin‐binding study

Abstract: A selection of lectins was used to investigate developmentally regulated changes in the distribution of cell surface oligosaccharides during the gastrulation and neurulation stages of early chick embryo development. Lectins from three specificity classes were used: glucose/mannose specificity (concanavalin A [Con A], Lens culinaris agglutinin [LCA], Pisum sativum agglutinin [PSA]); N-acetylglucosamine specificity (Lycopersicon esculentum agglutinin [LEA], wheat germ agglutinin [WGA], succinylated WGA [sWGA]); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
(46 reference statements)
1
11
0
1
Order By: Relevance
“…This difference in staining probably reflects developmentally regulated changes in the distribution of cell surface oligosaccharides and our findings thus corroborate those of Griffith and Sanders (1991) and Nico et al (1998) in earlier developmental stages.…”
Section: Discussionsupporting
confidence: 78%
“…This difference in staining probably reflects developmentally regulated changes in the distribution of cell surface oligosaccharides and our findings thus corroborate those of Griffith and Sanders (1991) and Nico et al (1998) in earlier developmental stages.…”
Section: Discussionsupporting
confidence: 78%
“…The use of lectins to probe specific glycans on cultured cell lines is well precedented (36,37). Lectins have enabled glycan visualization on tissue sections or whole-mount specimens at discrete time points in mouse (38), chick (39), and f ly (40) embryogenesis, as well as in the mature mouse thymus (41), rat endothelial vasculature (42), and human kidney (43). Further, lectins have been used to facilitate screening of Caenorhabditis elegans mutants with glycosylation defects (44,45).…”
Section: Imaging Glycans With Lectins and Antibodiesmentioning
confidence: 99%
“…The rapidity and complexity of the changes in carbohydrate residues during embryogenesis suggest that they play important roles for the development (3,5,14,26). During tooth development, Nakai et al (15) observed a moderate-to-strong binding of SBA in the stratum intermedium of well-differentiated ameloblasts.…”
Section: Discussionmentioning
confidence: 99%